TI_GERICHTE 52.2004.243 vom 20. Oktober 2004 , fornitura e posa di finestre in alluminio per uno stabile in costruzione - TI Tribunale d'appello (2004)
fornitura e posa di finestre in alluminio per uno stabile in costruzione